Exploration of local food ingredients: The effect of moringa leaf flour and sesame on the nutritional content of wet noodles - Vidianti, Della; Arifin, Ahmad David Royyifi; Fauziah, Lilia Faridatul; Purnamasari, Dwi Kurnia; Arum, Mentari Sekar; Meilina, Lita (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study aimed to develop wet noodles using Moringa oleifera leaf flour and sesame flour as local food alternatives with enhanced nutritional value to address calcium deficiency among adolescents. Calcium deficiency, a widespread issue affecting bone health, is often exacerbated by the consumption of nutrient-poor instant foods. This research explored the potential of local ingredients to improve noodle nutrition. Four formulations were tested: P0 (100% wheat flour), P1 (50% wheat flour, 30% Moringa leaf flour, 20% sesame flour), P2 (40% wheat flour, 25% Moringa leaf flour, 35% sesame flour), and P3 (60% wheat flour, 20% Moringa leaf flour, 20% sesame flour). Using a Randomized Complete Design, data were analyzed through ANOVA and Tukey HSD test. The results revealed that the substituted noodles had increased calcium, fat, and ash content, with reduced carbohydrate and moisture levels. Formulation P2 emerged as the most promising, containing 14.62% protein and 16 mg calcium content, making it a potential functional food product. This study underscores the importance of utilizing local ingredients to address the nutritional needs of adolescent while promoting innovative food solutions. Future studies should focus on evaluating storage stability, nutrient bioavailability, and commercialization prospects.